Copper Delivery to Chloroplast Proteins and its Regulation - Aguirre, Guadalupe; Pilon, Marinus (Frontiers in Plant Science, 2016)
Copper is required for photosynthesis in chloroplasts of plants because it is a cofactor of plastocyanin, an essential electron carrier in the thylakoid lumen. Other chloroplast copper proteins are copper/zinc superoxide dismutase and polyphenol oxidase, but these proteins seem to be dispensable under conditions of low copper supply when transcripts for these proteins undergo microRNA-mediated down regulation. Two ATP-driven copper transporters function in tandem to deliver copper to chloroplast compartments. This review seeks to summarize the mechanisms of copper delivery to chloroplast proteins and its regulation. We also delineate some of the unanswered questions that still remain in this field.